Development of natural underground ore mining technologies in energy distributed massifs - Lyashenko, Vasil; Khomenko, Oleh; Topolnij, Fedor; Golik, Vladimir (Technology audit and production reserves, 2019)
The object of research is the technology and facilities for underground mining of ores in the disrupted massifs. One of the most problematic places is the formation of man-made voids; which influence the occurrence and redistribution of stress-strain state (SSS) of the rock massif. Their existence in the earth’s crust provokes the influence of geomechanical and seismic phenomena; up to the level of earthquakes. The study used: – data from literature sources and patent documentation in the field of technologies and facilities for underground mining of ores in the energy-disrupted massifs of substantiation of technological parameters of operating units; – laboratory and production experiments; – physical modeling and selection of compositions of solidifying mixtures. Analytical researches; comparative analysis of theoretical and practical results by standard and new methods with the participation of the authors were performed. The questions of seismogeodynamic monitoring of the SSS of the rock massif during the safe development of rock-type ore deposits are considered. The interaction of natural and man-made systems providing geomechanical balance of ore-bearing massifs is shown. Possibilities of controlling the geomechanics of a massif with filling of man-made voids with various solid mixtures and tails of underground leaching of metals from substandard ores are investigated. The typification of processes is given and the distinctive features of underground block leaching of metals from rock ores are formulated in the aspect of controlling the geodynamics of the massif. The principle estimation of the combined technologies with rationalization of use of the SSS of the rock massif for regulation of the sign and magnitude of stresses in natural and artificial conditions is shown. The conclusions about the effectiveness of the controlled interaction of natural and man-made systems; ensuring the geomechanical balance of massifs and the earth’s surface in the area of subsoil development over a long period of time. The research results can be used in the underground development of ore deposits of complex structure of Ukraine; the Russian Federation; the Republic of Kazakhstan and other developed mining countries of the world.